INVESTIGATING FLY ASH-BOTTOM ASH-SOIL COMPOSITE AS SUSTAINABLE LINERS FOR URBAN LANDFILLS: GEOTECHNICAL AND ADSORPTION ASSESSMENT - Kartika Sari; Irwan Ridwan; Asiyanthi T. Lando; Sitti Hijraini Nur; Mehdi Tanha Zayarati (INDONESIAN JOURNAL OF URBAN AND ENVIRONMENTAL TECHNOLOGY, 2025)
This study investigates the combination of Fly Ash (FA), Bottom Ash (BA), and Soil (S) as a potential bottom liner in landfills. It is expected to cover the need for sustainable environmental technology, maintain structural strength, and prevent heavy metal pollution in rapidly urbanizing areas, while considering problems related to urban waste management. Aim: Evaluate FABA-Soil mixture as an alternative bottom liner material in landfill by assessing geotechnical performance and Cadmium (Cd) adsorption capacity. Methodology and results: The research explores two issues: mechanical stability (specific gravity, void ratio, compaction, and permeability) and mitigating Cadmium contamination from landfill leachate. Four mixture compositions (FBS1-FBS4), 15%, 30%, 50%, and 65% FABA content, were tested. Laboratory tests are conducted, including compaction, permeability, and adsorption continuous column tests. The results showed that intermediate FABA content (FBS2 and FBS3) may have stronger mechanical stability compared to others. For permeability, all values exceeded the regulatory standard. In the case of adsorption capacity, all compositions effectively removed Cd from the leachate. Conclusion, significance, and the impact study: Results on void ratio (e) and maximum dry density (MDD) suggested that a suitable mixture design may enhance long-term mechanical performance under a normal urban landfill loading situation. The FABA-soil mixture shows promise as an alternative landfill liner in moderate proportions and demonstrates excellent adsorption of heavy metals. All the attributes support general objectives of sustainable urban development and circular resource management, align with sustainable cities and communities, and responsible consumption and production.